2021
DOI: 10.3390/cryst11020116
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contribution of Solutal Marangoni Convection to Thermal Marangoni Flow Instabilities in a Liquid Bridge of Smaller Aspect Ratios under Zero Gravity

Abstract: The effect of solutal Marangoni convection on flow instabilities in the presence of thermal Marangoni convection in a Si-Ge liquid bridge with different aspect ratios As has been investigated by three-dimensional (3D) numerical simulations under zero gravity. We consider a half-zone model of a liquid bridge between a cold (top plane) and a hot (bottom plane) disks. The highest Si concentration is on the top of the liquid bridge. The aspect ratio (As) drastically affects the critical Marangoni numbers: the crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…When considering the combined e ect of thermal and solutal Marangoni ows for the uids with low Prandtl number and high Schmidt number, the primary bifurcation is from a 2D axisymmetric ow to an oscillatory three-dimensional ow. A recent study on the relative contribution of solutal Marangoni convection has shown that the ow bifurcations of high-Prandtl-number uids and high-Schmidt-number uids are identical (see, for instance, Agampodi Mendis et al, 2021). In the system considered in the aforementioned studies, the thermal and solutal Marangoni ows developing in the bridge were in the same direction.…”
Section: Introductionmentioning
confidence: 97%
“…When considering the combined e ect of thermal and solutal Marangoni ows for the uids with low Prandtl number and high Schmidt number, the primary bifurcation is from a 2D axisymmetric ow to an oscillatory three-dimensional ow. A recent study on the relative contribution of solutal Marangoni convection has shown that the ow bifurcations of high-Prandtl-number uids and high-Schmidt-number uids are identical (see, for instance, Agampodi Mendis et al, 2021). In the system considered in the aforementioned studies, the thermal and solutal Marangoni ows developing in the bridge were in the same direction.…”
Section: Introductionmentioning
confidence: 97%
“…Their simulation results were in good agreement with the experimental data. Mendis et al [ 12 ] proposed a 3D numerical simulation model to investigate the effect of solutal Marangoni convection on flow instabilities in the presence of thermal Marangoni convection in a Si-Ge liquid bridge. Different aspect ratios were investigated for a disk with cold top and hot bottom surfaces under zero gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Marangoni convection is very common in many industrial applications, such as crystal growth [1][2][3], welding [4][5][6][7], and evaporation [8,9]. During crystal growth, the buoyancy convection is weakened under microgravity, and Marangoni convection becomes the dominant convection.…”
Section: Introductionmentioning
confidence: 99%